Optimizing Integrative Holistic Early Childhood Development in Mimika Baru Sub-district: An IFAS and EFAS Analysis - Wulandari, Sri; Formen, Ali (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study investigates the implementation of Integrative Holistic Early Childhood Development (IHECD) in Mimika Baru Sub-district, focusing on four kindergartens: TK Negeri 1 Mimika, TK Kartika VI-31, TK Advent Timika, and TK Ceria Cerdas. Utilizing IFAS (Internal Strategic Factor Analysis Summary) and EFAS (External Strategic Factor Analysis Summary), the research aims to evaluate the current conditions and recommend strategies for optimizing IHECD. An evaluative study method was employed, involving questionnaires and focus group discussions to gather data on internal factors such as leadership, educator quality, and infrastructure, as well as external factors including government support and community involvement. The findings reveal that all institutions have more strengths than weaknesses and more opportunities than threats, placing them in quadrant I of the SWOT matrix, which indicates strong positions with significant growth potential. Despite these strengths, challenges such as inadequate infrastructure and insufficient health and safety measures were identified. The study underscores the need for tailored strategies to address these issues, suggesting that policymakers and stakeholders enhance support and resources to improve IHECD implementation. By focusing on strengthening internal capabilities and leveraging external opportunities, the overall quality of early childhood development services can be elevated, contributing to better educational outcomes and human resource development in the region. Furthermore, the research recommends a growth strategy for these institutions to maximize their strengths and opportunities. Future research should explore diverse settings, including rural areas, and consider longitudinal approaches to assess the long-term impact of recommended strategies. This comprehensive approach will ensure that all children in the Mimika Baru Sub-district have access to quality early childhood development services.